Pengaruh Penerapan Model Pembelajaran PjBL (Project Based Leaerning) Dengan Kegiatan Outdoor Learning Terhadap Hasil Belajar IPA Siswa Kelas VII SMP Pada Materi Pencemaran Lingkungan - Muthmainnah (Jumper: Journal of Educational Multidisciplinary Research, 2025)
Adolescents of productive age need many life skills to be able to compete and face the demands and challenges of real, everyday life. However, in reality, many teenagers still experience an inability to adapt due to an imbalance between their demands and their abilities, one of which is the ability formed from learning at school. This research aims to determine the effect of implementing the PjBL learning model with outdoor learning activities on science learning outcomes regarding Environmental Pollution for class VII students at SABIR Middle School. The research uses experimental methods with statistical tests. The results of the research show that tcount > ttable is 7.47 > 2.179, thus it can be concluded that the application of the PjBL learning model with outdoor learning activities has a significant effect on science learning outcomes on Environmental Pollution material for Class VII students at SABIR Middle School.